Contos novos, de Mário de Andrade: matrizes hipertextuais de uma célula dramática - Santos, Maria Aparecida da Silva (2010)
This dissertation is centered at the structural reading of the Mário de Andrade s anthology, CONTOS NOVOS and its discursive, discontinuous and innovated process of the literary tales genre. The chosen corpus is composed by the following stories: Vestida de Preto, O Peru de Natal and O Poço. These stories present specifics aims: To illustrate the geniality of the author about the enlargement of the limits of his esthetic scheme of the literary tales genre; the modern man and his alterity which comes from his identity; the questions about o fazer literário ; the transgression of literary language; the linguistics experiments; the Brazilian language assimilation and stylization; the textual performance of the storyteller, the character, and the reader, who is merged in hypertextual connections suggested by the main subject of the literary tales. Our hypothesis is very well demonstrated and supported by the subsequent authors and their theories: Mikhail Bakhtin, Julio Cortázar, Ricardo Piglia, Manual Bandeira, Edgar Allan Poe, Alfredo Bosi, Afrânio Coutinho, Massaud Moisés, André Jolles, Paul Zumthor, Pierre Lévy, and Wayne Booth, among other ones. It is also supported by Mário de Andrade s interview, as well as by his private letters and articles. This academic study exposes the subthemes as follows: The first chapter exibites an idea about the course, the structural features and the metamorphosis of the literary tales genre, including the oral tradition and even the modern literary writing. This chapter also lists the Brazilian tales writers, mainly Mário de Andrade, in the context of the modernism; his latest guidelines and connections, according to the non-linear logic, antecipating the structure of the modern novel. The second chapter describes the multifaceted narrative process, the storyteller and his many-sided expressions in CONTOS NOVOS: interconnections between first- person tales, which is showed by the storyteller-character relationship: from the oral to the written word. The third chapter demonstrates our focal hypothesis that says about the hypertext structure which is inside the multi-linear system of the CONTOS NOVOS; This chapter shows the importance of the memory and of the imaginary word in the construction of the narrative process and also shows all the experimental procedures of the storyteller-character, relating memory experience: interaction, alterity and identity are in the base of the new hypertextual content in a dramatic unit